Forage yields and nutritive values of oat and triticale pastures for grazing sheep in early spring - Oral, Hulya Hanoglu (Peerj Inc, 2024)
Background. Small-grain winter cereals can be utilized as early spring pastures in temperate climates to relieve grazing pressure and potentially mitigate feed shortages. This study was conducted to determine the effects of triticale and oat cereal pastures grazed by sheep during early spring on forage yields, nutritive values, and nutritional requirements of sheep. Methods. The research was carried out over three consecutive years, from 2015 to 2017, at the Sheep Research Institute in Band & imath;rma-Bal & imath;kesir, located in the Marmara region of T & uuml;rkiye. The treatments were arranged in a completely randomized block design, with the two forage species, triticale and oat, randomized within each of three blocks. The animal material for the study consisted of 24 Karacabey Merino sheep, each 2 years old, with an average live weight of 57.6 +/- 0.5 kg, all in the late lactation stage. In each replication, four sheep were included, resulting in a total of 12 sheep grazing in each of the triticale and oat pastures. The sheep grazed exclusively on the cereal pastures without any additional feed, and had unrestricted access to water throughout the entire period of the experiment. The dry matter yields (DMY), dry matter intakes (DMI), nutritive values, and mineral contents of the cereal species were determined. Results. The DMY showed significant differences over the years (P < 0.05). No differences in DMY were observed between pastures, with oats yielding 11.99 t ha(-1) and triticale yielding 11.08 t ha(-1). During the grazing period, the change in DMY was significant in all years (P < 0.05). The average DMI of the sheep was 2,003.5 g d(-1) for triticale and 2,156.6 g d(-1) for oat, respectively, and DMI exhibited no significant differences across pastures. Although there was no difference in DMI between 2015 and 2016, the lowest consumption occurred in 2017 (P < 0.05). Additionally, while DMI showed different trends each year based on the periods, it generally decreased by the end of the grazing period. While both pastures provided similar nutritive values, significant differences were observed in the crude protein (CP), acid detergent fiber (ADF), in vitro true DM digestibility (DDM), and metabolisable energy (ME) values across the years. Over the years, as the grazing period progressed, CP levels decreased while neutral detergent fiber (NDF), ADF, and acid detergent lignin (ADL) increased, resulting in reduced DDM and ME values. The phosphorus (P) content in triticale was higher than in oats, but there were no differences in the content of other minerals between them. Between the years, significant differences were observed in the levels of phosphorus (P) and iron (Fe), while changes in other elements were insignificant. The variation in mineral content during the grazing process differed over the three years. Study results indicated that the nutritional values of triticale and oat pastures are similar, and both can effectively be used to provide sufficient feed to meet the early spring forage requirements for sheep.
Keywords: Small grain winter cereals; Oats; Triticale; Dry matter yields; Dry matter intake; Nutritive value; Mineral contents; Sheep nutrition